The Psychological Sanctuary: Exploring the Prophet’s Sleep Habits in Seerat-e-Nabwi - Imtiaz, Maria; Tariq, Toseef (Seerat Studies, 2025)
Seerat-e-Nabwi, the biography of Prophet Muhammad (PBUH), is not just a history reading; it shows the way people should behave, their spirituality, and the state of their minds. The prophet's sleep habits - Qailulah (midday nap), Tahajjud (night prayer), and right-side sleeping - were the main events of his biography, which also had a tremendous psychological impact. These habits, based on faith, discipline, and simplicity, also reflected a lifestyle that was both physically and spiritually balanced. As a result, they provided the world with a new perspective on mental health that is easily relatable to both Islamic tradition and modern science. This paper examines the information on the sleep habits of Prophet Muhammad (PBUH) as mentioned in Seerat-e-Nabwi and Hadith literature, presenting it as a holistic framework for psychological well-being from an Islamic perspective. The paper successfully merges Quranic verses, Prophetic Traditions, and empirical data on sleep hygiene and mental health by employing a hermeneutical method from uṣūl al-tafsīr and ḥadīth criticism in conjunction with qualitative health research. This research work highlights several points where the Model of the Prophet as an anticipator of Modern Sleep Science Principles is close to being true, and, at the same time, it does not rule out that the Model is endowed with further metaphysical and moral dimensions beyond those already known. The model of the study that releases science principles of modern sleep in the prophetic heritage tradition not only brings together, through the acknowledgment of sleep as worship, spiritual practice, and contemporary health discourse, but also extends further horizons of spirituality in the Muslim context, therefore, opening a new area of the psychological domain that is culturally rooted.